La peinture métaphorique de la guerre dans Savochoun de Simine Daneshvar - Farideh Alavi; Zeinab Rezvantalab (Babel: Littératures Plurielles, 2020)
Simin Daneshvar, novelist, translator, famous Iranian literary woman was only 18 years old when the Allies invaded her country. 24 years after the Second World War, in his masterpiece, Savoshoun, she shows her hometown, Shiraz, sacked by the invasion of Allied troops, occupied by the British army. On the metaphorical and analogue mode, she portrays the Iranian people, always a victim of war. To describe tyranny and expansionism, the writer uses indirect turns, and stylistic methods that privilege the implicit. As an array of poetics, the metaphor is Daneshvar’s favorite trick to offer the reader an interpretative path, with which he reaches a greater meaning. In describing the war with a look both historicizing and literary, metaphorical painting favors the writer’s expression of an elliptical language. Daneshvar responds to the censorship imposed by the occupants, through metaphors inserted into a novel of resistance to the occupation, exploitation, and colonization. This article aims to detect the representation of the war in the metaphorical speech of Simine Daneshvar, which not only upsets the reader by addressing topics such as violence, absurdity and brutality, but is also invested with a power of persuasion served by an ingenious and innovative imagination.